MODELLING AND ANALYSIS OF POWERTRAIN PERFORMANCE OF A SINGLE-SEATED RACE CAR - ONG, ZI CONG (2018)
The project is aimed to optimize powertrain form a single seated race car in terms of speed, acceleration and achieve fastest lap time based on road and weather condition of the race track. The analysis process including modeling and simulation will be carried out to optimize the powertrain of the racecar. The racecar will be participating in Formula SAE competition where the vehicle will be put under various tests to examine its performance. The dynamic events of the competition includes acceleration test, skip pad test, autocross test, efficiency test and endurance test. Despite the importance of every events of the competition, the scope of this project will be focused on gaining as much points as possible in endurance event where the speed of the vehicle and the lap time will be the main focus area. Simscape Driveline in Matlab Simulink will be utilized to perform modeling and simulation of vehicle powertrain due to its easy application and accuracy. Technical understanding of each components in vehicle powertrain is crucial. Defining parameters and types of simulation block models is mandatory steps before starting the modeling and simulation activities. The block models from Simulink library will be utilized along with defined parameters for each block to form a complete vehicle model. Then, simulation will be run using different parameters obtained from different powertrain components as well as road and weather condition to analyze the overall performance of the vehicle powertrain. The obtained results will be compared to the existing results to determine the competency of the racecar to participate in the race. As shown in the result section, the best result obtained top speed of 42m/s and 29.27m/s of average speed which is comparable to the other participant’s achievable time.